A Feasibility Study to Examine the Role of Acupuncture to Reduce Symptoms of Lymphoedema after Breast Cancer: A Randomised Controlled Trial. Issue 5 (October 2014) - Smith, Caroline A; Pirotta, Marie; Kilbreath, Sharon
Objective: To determine the feasibility, acceptability and safety of using acupuncture to treat arm lymphoedema in women following treatment for breast cancer. Methods: We conducted a randomised controlled trial of acupuncture compared with treatment as usual. Twenty women with stable unilateral intransient lymphoedema present for at least 6 months were recruited from Sydney, Australia. The women received 12 acupuncture treatments administered to body and arm points on the non-lymphoedematous limb over 8 weeks, twice weekly for 4 weeks then once weekly for 4 weeks. Outcome measures included an assessment of interest to participate in the trial, identification of successful recruitment strategies, the appropriateness of eligibility criteria and compliance with treatment attendance. Clinical outcomes were assessed at baseline and 8 weeks and included extracellular fluid, lymphoedema symptoms, well-being and safety. Results: Acupuncture was an acceptable intervention in women with upper limb lymphoedema. Compliance with the treatment protocol was high, with nine women completing all 12 treatments. Outcome forms were completed by 17 women at 8 weeks. No major adverse occurrences, as defined by the study protocol, were reported from the acupuncture group although one woman found the needling uncomfortable, and no study participant experienced an increase in swelling of >10%. There was no change in extracellular fluid or any patient-reported outcome measurement. Conclusions: Lymphoedema is a persistent symptom experienced by women recovering from breast cancer. Our study suggests that acupuncture may stabilise symptoms and no major safety concerns were identified, so further research is needed. Trial Registration Number: Australian New Zealand Clinical Trials Registry, http://www.anzctr.org.au ACTRN12612000607875.